Penerapan Metode ELimination Et Choix Traduisant la REalite (ELECTRE) dan Weighted Product (WP) pada Sistem Pendukung Keputusan Deteksi Dini Penyakit Stroke - Karmia Larissa Br Pandia; Arief Andy Soebroto; Eko Arisetijono Marhaendraputro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Stroke is a sudden brain disorder caused by vascular disorders and can cause death that lasts for 24 hours or more. According to the WHO report in 1999, stroke was ranked second in the world in the highest mortality rate. In Indonesia, according to Riskesdas data from the Indonesian Ministry of Health, there was an increase in the probability of having a stroke by 8.3 per mile in 2007 to 12.1 per mile in 2013. This is evidence that there has been an increase in the number of stroke patients in Indonesia from the year 2013. from year to year, the Government has not found a solution to prevent stroke. Stroke is a disease that must be treated quickly because it can cause disability or death. Therefore, the problem of stroke requires a system that makes it easier for a health expert to detect stroke risk so that it can reduce the number of stroke risk patients. In this system, the ELECTRE method and weighted product are used to detect early risk of stroke because both methods can eliminate patients who are not in accordance with the characteristics and can choose the best alternative and classify stroke patients into high, medium and low categories. Based on the test results comparing the results of detection by the system with the results of manual detection with 30 test data, the accuracy value is 86%.